Berberine Alleviates Non-alcoholic Steatohepatitis Through Modulating Gut Microbiota Mediated Intestinal FXR Activation - Shu, Xiangbing; Li, Meng; Cao, Ying; Li, Chunlin; Zhou, Wenjun; Ji, Guang; Zhang, Li (Frontiers in Pharmacology, 2021)
Berberine is a natural plant alkaloid isolated from a diverse range of genera, it obtains anti-inflammatory, anti-obesity, and hepatoprotective properties, and is a promising agent for non-alcoholic steatohepatitis (NASH). Farnesoid X receptor (FXR) is a bile acid receptor and a drug target for NASH, however, the underlying mechanisms of berberine on regulating FXR are still unknown. In the present study, we feed mice with a 12-week high-fat diet with interval dextran sulfate sodium (0.5% in drinking water) diet to induce NASH, and treat the mice with berberine (100mg/kg per day) via oral gavage for additional 4 weeks. We demonstrate that administration of berberine alleviates steatosis and infiltration of inflammatory cells in the liver of NASH mice. We apply 16S ribosomal DNA sequencing to screen the structure of gut microbiota, and ultra-performance liquid chromatography-tandem mass spectrometry analysis to determine the bile acid profiles. The results show that berberine modulates gut dysbiosis, and specifically increases the relative abundance of Clostridiales, Lactobacillaceae, and Bacteroidale. Berberine modulated microbiomes are associated with bile acid de-conjugation and transformation, which are consistent with the altered bile acid species (e.g., deoxycholic acid, ursodeoxycholic acid) upon berberine treatment. BA species that respond to berberine treatment are known FXR agonists, thus we performed quantitative Real Time-PCR and western blot to examine the FXR pathway, and find that berberine up-regulates intestinal FXR and fibroblast growth factor 15 (FGF15) expression, and the secretion of FGF15 further inhibits lipogenesis and nuclear factor-κB activation in the liver. Whereas the beneficial effects of berberine are blunted in FXR knockout mice. Our results reveal that berberine alleviates NASH by modulating the interplay of gut microbiota and bile acid metabolism, as well as the subsequent intestinal FXR activation.